Muscle Abscess due to Salmonella Enterica - Akkoyunlu, YASEMİN; AKKOYUNLU, YASEMİN; CEYLAN, Bahadir; IRAZ, Meryem; Elmadag, NUH MEHMET; ELMADAĞ, NUH MEHMET; ASLAN, Turan (My University, 2013)
Non typhoidal Salmonellae spp. causes clinical symptoms especially in neonates, infants, aged and immunocompromised patients. Hematogenous dissemination may occur in complicated cases whereas the formation of abscess is rare. A 61-year old woman presented to our hospital with pain and a mass in her left arm, without fever and leukocytosis. She was using methotrexate, corticosteroids and quinine for rheumatoid arthritis. She had a history of cervix cancer and was given radiotherapy and chemotherapy 3 years ago. Upon physical examination and magnetic resonance imaging, the mass was considered as an abscess and was surgically drained. Salmonella enterica spp. enterica was yielded in the culture of the drainage material. Ceftriaxon 2g/day was started intramuscularly and continued for 4 weeks. Salmonellosis is usually a self-limited disease, generally restricted to gastrointestinal tract and acquired following food poisoning. Management of Salmonella abscess requires a combination of antibiotherapy, surgical drainage and eradication of primary foci